Setting up an Emergency Medicine Training Program - Curry, C (Journal of Nepal Health Research Council, 2013)
This article presents the foundations for building an emergency medicine training program, particularly in an environment with limited resources. It describes the history of the development of EM, what it is, how EM is practised in a typical hospital emergency department and who else is building EM training programs. The experience of establishing EM training in Papua New Guinea provides a model for development in other resource-limited environments. Strategies to establish training and to build the credibility and role of EM within the health system are described. Keywords: emergency medicine; resource-limited environments; training.